STUDI KORELASI INDEKS PEMBANGUNAN PEMUDA (IPP) DENGAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI INDONESIA - Achmad Efendi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study aims to determine and analyze the significance of the relationship between the Youth Development Index and the Human Development Index in Indonesia. This research is quantitative research to obtain results in the form of values from the correlation between the youth development index and the human development index in Indonesia. The data used are secondary data obtained from literature studies. Data analysis and correlation test used the Spearman Rank Correlation test. The results showed a correlation between the Youth Development Index variable and the Human Development Index, with a significance value of 0.004. (0.004 <0.05), the correlation coefficient value is 0.485 so that the final result shows that the relationship between the two variables is unidirectionalKeywords: Youth Development Index, Human Development Index.